Factors Influencing Public Interest in Cash Waqf Linked Deposit: The Nazhir Program's Role - Raspati, Sevtian Bugi; Rini, Nova; Soma, Nova A Mukti (Jurnal Ragam Pengabdian, 2026)
Cash Waqf Linked Deposit (CWLD) integrates temporary cash waqf with Islamic bank deposits so that investment returns finance social programs while the principal is protected. Despite its institutional potential, public participation remains limited and the behavioral role of the nazhir program is insufficiently understood. This study examines whether knowledge, religiosity, trust, perceived benefits, and promotion influence public interest in CWLD, and whether the nazhir program transmits or strengthens those relationships. An explanatory, cross-sectional survey was conducted among 100 respondents with knowledge of or experience in cash-waqf products at five Indonesian Islamic banks. Data were measured on a four-point Likert scale and analyzed using PLS-SEM in SmartPLS 4.1.1.8. The measurement model met convergent-validity and reliability criteria, while the structural model explained 71.4% of the variance in CWLD interest. None of the five antecedents had a significant direct effect. Promotion produced a significant indirect effect through the nazhir program (β = 0.535, t = 3.570, p < 0.001). Supplementary interaction tests further showed that the nazhir program strengthened the effects of trust (β = 0.766, p < 0.001) and promotion (β = 0.699, p < 0.001). The findings indicate that visible, professional, and accountable nazhir programs are the institutional mechanism that converts communication and trust into participation.